OXPHOS genes analysis in the red mullet (Mullus barbatus Linnaeus, 1758) - Calogero, Giada Santa; Mancuso, Marco; Segvic-Bubic, Tanja; Ferrito, Venera; Pappalardo, Anna Maria (Frontiers in Marine Science, 2025)
Red mullet, Mullus barbatus Linnaeus, 1758, is a very important target species of high commercial value for small-scale fisheries in the Mediterranean Sea. The distribution of the species is wide encompassing the North-Eastern Atlantic (from Scandinavia to Senegal), the Mediterranean Sea and Black Sea. Climatic differences across its range could trigger specific bioenergetic demands due that ectothermic aquatic species exploit heat exchange with the external environment to regulate metabolic activities and adaptation. Mitochondrial OXPHOS (mtOXPHOS) genes are particularly involved in these processes and they have been studied in the last decades as a system that is subject to selection under determined environmental constraints. Based on the above considerations, the purpose of this work were to analyze the nucleotide sequences of the Cytochrome Oxidase I (COI) and Cytochrome b (Cytb) OXPHOS genes in seven Mediterranean populations of M. barbatus, living within a latitudinal range between the North Adriatic, the Strait of Sicily in the South, the Ionian Sea in the East and the Balearic Sea in the Western Mediterranean. The aims were to assess the genetic diversity in the studied populations and to detect the presence of positive selection on the two-target protein-encoded genes using tests of recombination and selection based on different models of evolution. The diversity indices indicated higher values of haplotype diversity in the Adriatic populations than in the remaining populations for both genes. Furthermore, a very high number of COI and Cytb private haplotypes was found in almost of populations. Signature of pervasive positive selection by FUBAR and episodic positive selection by MEME were exclusively detected in COI gene. Our results support the need to manage red mullet populations as separate sub-populations with distinct gene pools.